La quarta rivoluzione industriale tra opportunità e disuguaglianze - BANTI, ALBERTO MARIO; LAZZERONI, MICHELA (Nuove Geografie. Strumenti di lavoro, 2022)
In recent years a new revolution has been emerging, connected to the growth of advanced technologies (such as big data, algorithms, digital platforms, sensors) and to the intensity of their impact at the economic, social and cultural level. Within the debate on this so-called fourth industrial revolution, the text focuses on the analysis of the changes, both generated and perceived, with an emphasis on development opportunities and critical issues, as well as social and territorial inequalities. Considering contributions provided by some humanistic and social disciplines, the book introduces interdisciplinary research perspectives and explores new methods of analysis that combine the evolutionary dimension (typical of political history and economic history) with the spatial (prevalent in geography) and the narrative dimension (evident in cultural history and geography and in particular in disciplines related to image, representation, cinema).